ChemInform Abstract: K5Mo4O14F: A Novel Fluorinated Polyoxomolybdate and Its Structural Stability. Issue 36 (September 2015) - Gong, Pifu; Luo, Siyang; Kang, Lei; Jiang, Xingxing; Xu, Jing; Zhang, Guochun; Lin, Zheshuai; Wu, Yicheng; Chen, Chuangtian
Abstract Transparent colorless single crystals of K5Mo4O14F are grown from a melt containing KNO3 (flux), KBF4, and MoO3 in the molar ratio of 4:1:0.5, resp.